A study of students' use of restraint systems in school transportation services in primary and secondary schools in northern Iran: an observational study - Shahrokh Yousefzade-Chabok; Samira Azari; Leila Kouchakinejad-Eramsadati; Enayatollah Homaie Rad; Marjan Hosseinnia; Naema Khodadadi-Hassankiadeh (BMC, 2021)
Abstract Background Traffic accidents are one of the leading causes of death and severe injury among child occupants of vehicles in most countries. This has led to the consideration of how to use restraint systems for students in school buses. The purpose of the present study was to determine the percentage of students' use of restraint systems in school transportation services in 2020. Methods In the present cross-sectional observational study, seatbelt use was assessed in 400 students in school transport vehicles using a checklist. The observation team sat at their vehicle, at the nearest location on one of the three sides of the school's entrance: they had by manually registering the variable in the checklist. They focused on exactly the first vehicle parked next to the school entrance. There were two other observers to validate the observations. Data were analyzed by SPSS software (version 21). Results The rate of using restraint systems was 11.3%, use of restraint systems in the Sport Utility Vehicles (SUVs) was significantly higher (P < 0.03), in areas with medium income (P < 0.009) and low income (p < 0.012) as well as when the students were sitting in the rear seats, using the seatbelt were significantly lower (P < 0.001). Seatbelt use in students was less in services driven by drivers over the age of 40 (P < 0.01) and more in vehicles driven by female drivers (P < 0.003) and newer vehicles (p < 0.001). Conclusion School authorities must enforce traffic safety rules for school transportation services. These rules should be taught to drivers, families, and students. A restraint system must be mandatory for all students. School officials must equip their buses with seatbelts and employ school bus assistants to encourage wearing seatbelts and prevent students from standing.